Oil Revenue Assignments : Country Experiences and Issues - Mottu, Eric (IMF Working Papers; Working Paper, 2002)
Based on country experiences, the paper assesses policy options to assign oil revenues to subnational governments (SNGs). The literature recommends that oil revenues be centralized. Given political economy considerations, this paper suggests that a possible alternative is to assign stable oil-tax bases to oil-producing SNGs, supplementing these with predictable transfers from the center. Although commonly used, oil revenue-sharing arrangements are the least preferable solution, as they complicate macroeconomic management and do not provide stable financing. Revenue sharing also does not diffuse separatist tendencies, since oil-producing SNGs would still be better off by keeping their oil revenues in full.